The Crisis of Muslim History: Religion and Politics in Early Islam by Mahmoud M. Ayoub (Oxford, UK: Oneworld Publications, 2003. 179 pages.) (American Journal of Islam and Society, 2004)
A host of recent events – well known to all and not in need of rehearsal here– have had, among a variety of other consequences, the unexpected effect of focusing the world’s attention on the diversity of Muslims and the Islamic tradition.The constant talk of “Sunni triangles,” “Shi`ite clerics,” and “Wahhabiradicals,” however, raises important questions about what precisely dividesthe Muslim community along these lines. For Ayoub, the roots of this sectarianismcan be found, at least in part, in the crucial historical time periodknown as the Rashidite (or “Rightly Guided”) caliphate. It is the “politicaland socio-religious crisis” (p. 4) of this era (stretching from the death of theProphet until `Ali’s assassination) and its implications for subsequent generations,that form the subject matter of this book.Ayoub envisions his work as filling a void found in most general introductionsto Islam, which for all their other merits, often fail to provide a clearaccount of this formative period of Islamic history. As for those who haveventured to write in the area, Ayoub considers the works of both Muslim andwestern scholars to be fraught with the political and theological biases oftheir authors. His desire to avoid this pitfall motivates him to adopt thenovel approach of letting the “primary sources of Muslim thought and history”(p. 4) speak for themselves, a tack not unlike the one he uses in hisimportant contribution to tafsir studies: The Qur’an and Its Interpreters.Using this methodology, Ayoub seeks to construct and present a balancedaccount of the major historical events of the Rashidite era in an effortto explore the interaction between considerations of religion and politics inearly Islamic understandings of the nature of authority. His analysis of thevarious claims to the caliphate advanced by Abu Bakr, `Umar, `Uthman,and `Ali, as well as by less successful contenders, is aimed at supporting hiscentral assertion that because “the Prophet died without leaving a clearpolitical system” (p. 22), the Companions did not agree – indeed they vehementlydisagreed – on answers to questions of political authority: ...